Gender Equality in Cambodian Higher Education Institutions: A Case Study of the National University of Battambang - Touch , Sreynuth; Sok , Sreyneang; Ra, Reatrey; Makara, Sreyleak; Hoeun , Soukea; Sok, Khorn; Sam, Rany; Yoeng, Hak (MASI Mandiri Edukasi, 2024)
This study examines the gender distribution among students, faculty, and administrative staff at the National University of Battambang (NUBB). The research investigates the sociocultural, economic, and institutional barriers to gender equality at the university, assesses the effectiveness of existing gender equality policies and initiatives, and considers the role of university leadership in advancing gender equality and fostering an inclusive culture. A mixed-methods approach was used, combining quantitative surveys with qualitative interviews. The findings reveal that the number of female students significantly exceeds that of male students, yet women constitute less than 25% of the faculty and administrative staff. Despite this disparity, NUBB's commitment to implementing gender equality policies and initiatives is commendable. The university's leadership is dedicated to these efforts and actively supports advancing gender equality, which bodes well for the future. The researchers offer practical recommendations to enhance gender equality at NUBB, contributing to broader efforts to promote gender equity in Cambodian higher education institutions. The results underscore the ongoing need for policy revisions and sustained efforts to address gender imbalances and create a more equitable academic environment.